Polish Tax Reform "Polski Ład" – Consequences of Introducing Changes on the Example of Selected Flat-rate Tax Forms for Micro and Small Companies - Piotr KASPRZAK; Danuta BOIKE; Ewa ŁĄCZEK-TARAZEWICZ; Jarosław WRÓBLEWSKI (Communications of International Proceedings, 2022)
This article describes aspects related to the introduction of the latest tax reform in Poland. The changes initiated in January 2022, under the name Polski Ład, concern a wide range of tax changes in Poland. Reform, in a broad sense, is a multidimensional government development program, which is primarily aimed at getting out of the crisis caused by the COVID-19 pandemic and a smooth transition to financing strategic goals in investment areas. The main aim of the article is to present the most important aspects regarding issues related to the consequences of introducing changes in selected flat-rate tax forms for micro and small companies. The detailed objectives of the article are to present issues that affect the tax records using the tax card, and to show what restrictions are introduced by the Polish order in the tax card records system.
Keywords: tax reform; Polish Governance; crisis; corporate taxation; SME